Nocturnal non invasive ventilation in normocapnic cystic fibrosis patients: a pilot study: Non-invasive ventilation in cystic fibrosis - Papale, Maria; Parisi, Giuseppe; Spicuzza, Lucia; Rotolo, Novella; Mulè, Enza; Aloisio, Donatella; Manti, Sara; Leonardi, Salvatore (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: In patients with cystic fibrosis (CF) non-invasive ventilation (NIV) improves lung mechanics and gas exchange, and decreases the work of breathing. Domiciliary NIV is mainly used in hypercapnic patients with severe disease, because it counteracts the progression of lung functional impairment and it is often used as a useful “bridge” to lung transplantation. However, to date, there are no standardized criteria to indicate the effect of a precocious starting of NIV in patients with functional ventilation inhomogeneity without hypercapnia. In this pilot study we assessed whether an early NIV treatment might influence functional and clinical outcomes in CF patients.Methods: Six normocapnic CF patients were treated for one year with NIV. At baseline and after 1 year of NIV treatment, arterial gas analysis, spirometry, MBW to derive LCI, nocturnal cardio-respiratory polygraphy (PG), and Pittsburgh Sleep Quality Index (PSQI) were perfomed in all enrolled patients.Results: After one year, despite spirometric and LCI values remain statistically not modified, the number of infectious exacerbations was reduced by 50%.Conclusions: These results suggest that nocturnal NIV improves clinical conditions of stable CF patients. Finally, we suggest that this procedure can be useful to counteract the progression of lung disease even in normocapnic patients